The interactive influence of borderline personality disorder symptoms and social comparison orientation on self-esteem. (April 2021) - Richmond, Julia R.; Edmonds, Keith A.; Rose, Jason P.; Gratz, Kim L.
Abstract: Despite evidence for an association between BPD symptoms and low/unstable self-esteem (SE), no research has examined social factors that may moderate the relation between BPD symptoms and SE difficulties. One factor that may be especially relevant is social comparison orientation (SCO). Across two studies, this research examined the main and interactive effects of BPD symptoms and SCO on several SE outcomes, including trait SE, baseline state SE, and in-the-moment threat to SE following an online social interaction task. In Study 1, a university sample of young women ( N = 161) completed questionnaires on BPD symptoms, SCO, and trait SE. In Study 2, a university sample of young adults ( N = 108) completed questionnaires on BPD symptoms, SCO, and baseline state SE. Participants engaged in a rejection or inclusion condition of an online social interaction task and reported on in-the-moment threat to their SE. Results revealed significant relations between BPD symptoms and all SE outcomes among young adults with high and mean SCO. Results highlight the relevance of SCO to the relation between BPD symptoms and SE, suggesting that BPD symptoms are associated with lower trait and state SE and greater threat to SE among young adults with average or greater tendencies to socially compare. Highlights: Borderline personality disorder (BPD) is related to low/unstable self-esteem (SE). SCO moderates relation between BPD and trait and baseline state SE. BPD symptoms are related to threat to SE following a social interaction task. Individuals with high BPD symptoms and high SCO may have greater SE difficulties.